Comparative proteomics analysis of oral cancer cell lines: identification of cancer associated proteins - Karsani, S.A.; Saihen, N.A.; Zain, R.B.; Cheong, S.C.; Rahman, M.A. (BMC, 2014)
Background A limiting factor in performing proteomics analysis on cancerous cells is the difficulty in obtaining sufficient amounts of starting material. Cell lines can be used as a simplified model system for studying changes that accompany tumorigenesis. This study used two-dimensional gel electrophoresis (2DE) to compare the whole cell proteome of oral cancer cell lines vs normal cells in an attempt to identify cancer associated proteins.